KOORDINASI PADA PROSES PENYUSUNAN RENCANA PRIMA TANI DALAM MENDUKUNG PEMBANGUNAN DAERAH DI DESA HARGOBINANGUN, KECAMATAN PAKEM, KABUPATEN SLEMAN - Endang Wisnu Wiranti; Ageng Setiawan Herianto; Roso Witjaksono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
A proper coordination process of an integrated development program, such as PRIMATANIN is not well understood by the development program manager. The research objectives are to assess the coordination process in formulating a PRIMATANI development plan; and to identify its influencing factors. The research was conducted in Hrgobinangun village of Sleman District. Method of this research was a qualitative method with a case study. The data collection and anlyiss was conducted using an in-depth interviews method and a documentary analysis on the coordination meeting of PRIMATANI. The result shows that the imperfect coordination process in this program was caused by asymmetric communication process whisvh dominated solely by the Department of Agriculture in determining this targeted village and its decelpment program. In order to support the integrated development program, the coordination process among the technical department shiuld be formalized since the targeted area determination. Then, it should be followed by a formal agreement among the departments on development program formulation plan and regular information supply on their corrdination meeting.